2014
DOI: 10.3233/jvr-140690
|View full text |Cite
|
Sign up to set email alerts
|

Virginia's self-determination project: Assisting students with disabilities to become college and career ready

Abstract: The Virginia Department of Education's I'm Determined project is a statewide initiative designed to engage students with disabilities as early as elementary school to learn and demonstrate self-determined skills. This article will focus on information and suggested strategies to use with middle and high school students to assist in their transitions to become college and career ready.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Altering classroom environments to support autonomy, competence, and relatedness is one way to reproduce the supports that led to these participants’ success. The three I’m Determined tools, namely, One-pager, Goal plan, and the Good Day plan, have been successfully used with students with LD, special education teachers, and general education teachers to increase autonomy, competence, and relatedness at the classroom and building levels (Moore & McNaught, 2014). In addition, this study’s participants revealed the need to know more about their LD and how to be successful with it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Altering classroom environments to support autonomy, competence, and relatedness is one way to reproduce the supports that led to these participants’ success. The three I’m Determined tools, namely, One-pager, Goal plan, and the Good Day plan, have been successfully used with students with LD, special education teachers, and general education teachers to increase autonomy, competence, and relatedness at the classroom and building levels (Moore & McNaught, 2014). In addition, this study’s participants revealed the need to know more about their LD and how to be successful with it.…”
Section: Discussionmentioning
confidence: 99%
“…As leaders, youth are required to participate in two multiday, face-to-face training sessions per year and monthly web-based calls focusing on the core components of self-determination, including decision-making, goal-setting, self-advocacy, and problem-solving (Moore & McNaught, 2014). The multiday training is delivered by Determinators and veteran youth leaders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple scholars have noted a relationship between student involvement in the IEP process and self-determination skills (Cavendish et al, 2017; Rodriguez & Cavendish, 2013). Self-determination refers to behaviors such as self-advocacy, goal setting, and self-awareness that allow an individual to serve as the primary causal agent in their own life (Moore & McNaught, 2014; Wehmeyer, 2006). The essential core components of self-determination include: choice making, decision making, problem solving, goal setting and attainment, self-observation, self-evaluation, self-reinforcement, self-instruction, self-advocacy and leadership, internal locus of control, self-efficacy and outcome expectancy, self-awareness, and self-knowledge (Wehmeyer et al, 1997).…”
Section: What Is Self-determination?mentioning
confidence: 99%
“…Children with disabilities experience higher rates of social-emotional issues, which have long-term implications for an increase in the risk of further disabilities being diagnosed, as well as links to poverty and Supplemental Security Income dependency (Lee et al, 2016). In addition, children with disabilities often show deficits in transition and career success and require interventions to increase self-determination (Moore & McNaught, 2014; Zheng et al, 2014). Childhood mental health issues along with other emotional and behavioral problems are also increasing as ADHD and other disabilities are becoming more prevalent (Currie & Kahn, 2012).…”
Section: Introductionmentioning
confidence: 99%